Commentaries on the Trade Regime - Atsain, Achi; Tshibaka, Tshikala B. (International Food Policy Research Institute, 1987)
Oyejide's chapter poses the problem of choice of policy instruments. As political motivations dominate in many countries in sub-Saharan Africa, the choice of policy instruments has been very often erratic. Oyejide clearly illustrates this dilemma. Protection under an inward-looking regime combined with overevaluation has directed resources away from the agricultural sector in Nigeria, inflicting heavy cost on rural consumers and producers while subsidizing urban consumers. In many other countries, particularly Ivory Coast, an outwardlooking policy limited protection of the industrial sector, and sound fiscal and distributional policies have raised incomes in rural areas and maintained a steady increase in export commodity and food production.